1996
DOI: 10.1021/tx950116m
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cytochrome P450 3A4 Enzyme in the N-Demethylation of Methadone in Human Liver Microsomes

Abstract: Methadone has become one of the most widely used drugs for opiate dependency treatment. This drug is extensively metabolized by the cytochrome P450 hepatic enzyme family in man, yielding an N-demethylated metabolite that cyclizes spontaneously into 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine. The specific forms of cytochrome P450 involved in this oxidative N-demethylation were examined in a panel of 20 human liver microsomal preparations previously characterized with respect to their P450 enzyme contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
3
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(172 citation statements)
references
References 38 publications
6
161
3
2
Order By: Relevance
“…Methadone is primarily metabolized by the cytochrome P450 enzyme system, specifically CYP3A4, to 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) [25][26][27]. Although not a substrate for glucuronidation itself, methadone inhibits the glucuronidation of 3 ′ -azido-3 ′ -deoxythmidine (AZT) in vitro [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methadone is primarily metabolized by the cytochrome P450 enzyme system, specifically CYP3A4, to 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) [25][26][27]. Although not a substrate for glucuronidation itself, methadone inhibits the glucuronidation of 3 ′ -azido-3 ′ -deoxythmidine (AZT) in vitro [28].…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, it was also observed that methadone-maintained subjects had higher plasma morphine concentrations than non-opioid-dependent controls when given the same i.v. dose, suggesting decreased morphine clearance in this population.Methadone is primarily metabolized by the cytochrome P450 enzyme system, specifically CYP3A4, to 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) [25][26][27]. Although not a substrate for glucuronidation itself, methadone inhibits the glucuronidation of 3 ′ -azido-3 ′ -deoxythmidine (AZT) in vitro [28].…”
mentioning
confidence: 99%
“…9) In addition, quercetin is known to be a reversible inhibitor of CYP3A4 activity. 15) Therefore, quercetin contained in onion may be considered to be a major inhibitory component in the mixture of orange vegetables juices.…”
Section: Discussionmentioning
confidence: 99%
“…Methadone is a racemic synthetic opioid that acts by binding the μ-opioid receptor, with the affinity for the R-enantiomer being 10 times higher than that for the S-enantiomer [74]. Methadone is a substrate of CYP2B6 and 2C19 and also of pgp, while the role of CYP3A4 remains debated [75,76]. When methadone maintenance patients were started on NNRT Is such as efavirenz and nevirapine, methadone AUCs were observed to decrease to 55 and 63 %, respectively, precipitating withdrawal in nine out of 10 participants [77,78].…”
Section: Sedative Hypnotics and Opioid Medicationsmentioning
confidence: 99%